FACTORS INFLUENCING EMPLOYEE ENGAGEMENT IN EDUCATIONAL ORGANIZATION - Manivannan, S.K.; Sanchita, YRM (International Journal of Psychosocial Rehabilitation, 2020)
Aim of this research is to identify the factors that determine employee engagement in the context of educational organizations. Companies put in enormous investments to build competitive advantage in human capital by developing employee engagement and commitment. Though these indicators are increasing, yet despite the increase in spending, research indicates levels of employee commitment and engagement are not improving in line with the spend, possibly making employee-generated competitive advantage in question. Hence this study was undertaken to identify the current engagement level of employees and its impact on organizational effectiveness and to recommend suggestions to overcome ineffectiveness in these measures through appropriate employee engagement initiatives.